G.C base pair in parallel-stranded DNA--a novel type of base pairing: an ab initio quantum chemical study - Sponer, J; Hobza, P (Journal of biomolecular structure & dynamics, 1994)
It was shown recently that parallel stranded DNA also incorporates the Reverse Watson-Crick Guanine. Cytosine (RWC G.C) pair. It contains only one hydrogen bond surrounded by mutual carbonyl group and amino group contacts. Here we describe an ab initio quantum chemical analysis of this unusual base pair. The conclusions can be summarized as follows. (1) The RWC G.C base pair exhibits a previously unknown type of DNA base pairing. (2) Its stabilization energy is estimated to be above 20 kJ/mol. A significant part of the stabilization originates in attractive interactions between the amino group hydrogen atom on one base and lone electron pair of the amino group nitrogen atom of the other (opposite) base. (3) In contrast to any other base pairing patterns, observed in the DNA molecules, the two DNA base amino groups in the RWC G.C base pair are highly nonplanar. They can form additional bifurcated hydrogen bonds with neighboring base pairs. Coplanarity of the two DNA base rings is energetically acceptable. (4) The unique RWC G.C pair cannot be analyzed by the empirical potential calculations.
Keywords: termodynamika; vodíková vazba; konformace nukleové kyseliny; cytosin; Nucleic Acid Conformation; Quantum Theory; Computer Simulation; guanosin; DNA; kvantová teorie; počítačová simulace; zastoupení bazí; Hydrogen Bonding; Guanosine; Thermodynamics; chemické modely; Base Composition; Cytosine; Models, Chemical